2022
DOI: 10.3389/fnut.2022.936229
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorn fruit acid consumption attenuates hyperlipidemia-associated oxidative damage in rats

Abstract: ContextHyperlipidemia is a highly prevalent risk factor for atherosclerosis and stroke. The currently available medications used to treat Hyperlipidemia cannot improve its oxidative stress damage. Consumption of hawthorn can regulate blood sugar and blood lipids, and its rich fruit acid is a natural antioxidant that can improve oxidative stress damage.ObjectiveThe present research aimed to investigate the protective effect of hawthorn fruit acid (HFA) on hyperlipidemia and to determine its potential molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Wu et al ( 31 ) found that the substrates of G. frondosa decreased glutathione (GSH) and catalase activity, increased GSH peroxidase activity, inhibited oxidative stress, and increased bile acid synthesis to improve hypercholesterolemia. Feng et al ( 32 ) administered hawthorn fructofuranic acid (HFA) to rats. Found that activation of Nrf2/HO-1 signaling pathway could inhibit oleic acid (OA)-induced oxidative damage in a hepatocellular carcinoma cell line (HepG2), which in turn reduced oxidative stress damage in rats, effectively reduced triglyceride and cholesterol levels, attenuated hepatic steatosis and intervened in hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al ( 31 ) found that the substrates of G. frondosa decreased glutathione (GSH) and catalase activity, increased GSH peroxidase activity, inhibited oxidative stress, and increased bile acid synthesis to improve hypercholesterolemia. Feng et al ( 32 ) administered hawthorn fructofuranic acid (HFA) to rats. Found that activation of Nrf2/HO-1 signaling pathway could inhibit oleic acid (OA)-induced oxidative damage in a hepatocellular carcinoma cell line (HepG2), which in turn reduced oxidative stress damage in rats, effectively reduced triglyceride and cholesterol levels, attenuated hepatic steatosis and intervened in hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive intake of high-fat diet (HFD) leads to an increase in plasma cholesterol levels, thereby posing a serious threat to cardiovascular health in humans (8). Studies have shown that chronic and excessive intake of HFD leads to adipose deposition in visceral organs (perirenal and epididymal adipose tissue), increasing chronic inflammation and leading to damage due to oxidative stress (9)(10)(11). Therefore, inhibition of chronic inflammation and oxidative stress damage could be an effective strategy to reduce the risk of metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The botanical drugs composed of XZP, including GP ( Dai et al, 2022 ; Rao et al, 2022 ), Hawthorn ( Peng et al, 2019 ; Feng et al, 2022 ) and FRR ( Song & Shen, 2021 ), have been extensively studied in regulating TC, TG, LDL-C, and HDL-C. Researches showed that GP extract increased AMPK activation and suppressed adipogenesis by decreasing the mRNA expression of encoding CCAAT/enhancer binding protein-α (C/EBPα), peroxisome proliferator-activated receptors γ (PPARγ), sterol regulatory element-binding protein 1c (SREBP1C), and fatty acid synthase (FAS) ( Park et al, 2014 ; Wang B. et al, 2020 ). In addition, GP extract elevated phosphatidylcholine metabolism decreased the level of trimethylamine N-oxide for antihyperlipidemia effect ( Wang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%